Kontribusi Guru PAI dalam Mengembangkan Kecerdasan Spiritual Peserta Didik Kelas VIII di MTS Ma’arif NU 1 Kemranjen Banyumas - Khasna Khanifah, Jihan; Sahnan, Ahmad (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to describe the contribution of Islamic Education (PAI) teachers in developing the spiritual intelligence of eighth-grade students through religious activities at MTs Ma'arif NU 1 Kemranjen, Banyumas. Spiritual intelligence is one of the essential aspects in shaping the character and personality of students in a balanced manner—intellectually, emotionally, and spiritually. Islamic Education teachers play a strategic role in instilling spiritual values through classroom learning as well as religious activities outside the classroom. This research employs a qualitative approach with a descriptive method. Data collection techniques include passive participant observation, semi-structured interviews, and documentation. The research subjects consist of Islamic Education teachers, eighth-grade students, and the head of the madrasah. Data analysis was carried out through data reduction, data display, and drawing conclusions. The results of the study indicate that Islamic Education teachers make a significant contribution to the development of students’ spiritual intelligence. Their contribution is manifested through their roles as motivators who encourage enthusiasm in worship, facilitators who provide facilities and a supportive environment for religious activities, role models in spiritual attitudes and behavior, and initiators of well-structured religious programs. These activities include congregational Dhuhr prayers, Qur’anic recitation (tadarus), the recitation of Asmaul Husna, memorization of Juz ‘Amma, mujahadah, and Friday charity activities (Jum’at Beramal). This study is expected to serve as a reference for teachers, educational institutions, and related parties in developing effective religious programs to enhance students’ spiritual intelligence.